(untitled) (Revista de História Regional, 2007)
Cholula and Ixtenco are two communities of mesoamericana indigenous tradition in Mexico. Its main economic activity is agriculture which is sustained in corn, beans, chili and squash, so and as one becomes from the pre-Hispanic time. In those communities, multidisciplinary studies have been made, between those of agronomy stand out, physical anthropology, archaeology, geography, cultural anthropology and, of course, history. With base in them, we presented an analysis of which the feeding, among other factors, it gave like result in the pre- Hispanic indigenous population and the one of end of century xx. The size of the individuals, after 500 years, it continues being practically the same one, and then their nourishing characteristics continue being, also, practically the same ones